Sharing the burden the Armenian question, humanitarian intervention, and Anglo-American visions of global order - Laderman, Charlie ca. 20./21. Jh (Oxford studies in international history, 2019)
The destruction of the Armenian community in the Ottoman Empire was an unprecedented tragedy. Theodore Roosevelt was adamant that it was the 'greatest crime' of the First World War. The mass killing of approximately one million Armenian Christians was the culmination of a series of massacres that Winston Churchill would recall had roused publics on both sides of the Atlantic and inspired fervent appeals to see the Armenians 'righted.' This text explains why the Armenian struggle for survival became so entangled with the debate over the United States' international role as it rose to world power at the turn of the twentieth century